2001
DOI: 10.1097/00005373-200104000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Chest Tube Removal: End-Inspiration or End-Expiration?

Abstract: Discontinuation of chest tubes at the end of inspiration or at the end of expiration has a similar rate of post-removal pneumothorax. Both methods are equally safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 10 publications
1
58
0
6
Order By: Relevance
“…In one study, the removal of the chest tube at the end of inspiration and at the end of expiration was compared, and the Valsalva maneuver was performed in both these groups. No difference was observed between these two groups in terms of the risk of pneumothorax (22). Experimental studies are needed in this regard for the elimination of technical differences, standardization of treatment and care, and use of a valid and reliable method.…”
Section: Discussionmentioning
confidence: 98%
“…In one study, the removal of the chest tube at the end of inspiration and at the end of expiration was compared, and the Valsalva maneuver was performed in both these groups. No difference was observed between these two groups in terms of the risk of pneumothorax (22). Experimental studies are needed in this regard for the elimination of technical differences, standardization of treatment and care, and use of a valid and reliable method.…”
Section: Discussionmentioning
confidence: 98%
“…Comparing drain removal during end-inspiration and end-expiration, Bell et al (2001) found no difference in the rates of post-removal pneumothorax, although current practice recommends drain removal whilst the child performs a Valsalva manoeuvre or else during expiration. A smooth, swift removal of the drain is preferred to a slow withdrawal.…”
Section: Removal Proceduresmentioning
confidence: 90%
“…24 Bell and colleagues conducted a prospectively compared removal of 102 chest tubes in 69 trauma patients either at end inspiration or end expiration and found no significant difference in the incidence of recurrent pneumothorax. 25 Although unstudied, our practice is to return a previous water seal system to suction for a brief period before removal. This "might help, can't hurt" approach may remove residual air or fluid from the tubing and pleural space.…”
Section: Chest Tube Managementmentioning
confidence: 99%